Development of a formalized scheme of hydrocarbon transformations in the catalytic cracking for forecasting the individual composition of gases - Nazarova G. Yu. Galina Yurievna; Oreshina A. A. Aleksandra Aleksandrovna; Kaliev T. A. Toleubek Arystanbekovich; Arkenova S. B. Sania Bolatovna; Antonov A. V. Artem Viktorovich; Lemeshko E. Yu. Elena Yurievna (2020, 2020)
Title screen